2011
DOI: 10.1007/s10461-011-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

Early Adolescent Romantic Relationships and Maternal Approval among Inner City Latino Families

Abstract: Latino youth are at high risk for acquiring HIV during adolescence. The present study documented the nature of adolescent romantic relationships among 702 Latino eighth grade students and their mothers in the Bronx, NY. The study examined adolescent romantic relationships, the association between participation in such relationships and intentions to engage in sexual risk behavior, and maternal influences on adolescent's involvement in intimate behaviors in romantic relationships. Almost 50% of youth had been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…Boys were significantly more likely to perceive that their mothers approved of their sexual behavior, including holding hands with a partner, kissing, and sexual intercourse. This study also found that adolescents' perceived maternal approval was greater than actual maternal approval for both genders, suggesting that adolescents see mothers as being more supportive of their sexual behaviors than they actually are (Bouris et al, 2012). Latino adolescents' perception that their mothers approved of their sexual behaviors parallels research among American Indian youth.…”
Section: Family Influencessupporting
confidence: 56%
“…Boys were significantly more likely to perceive that their mothers approved of their sexual behavior, including holding hands with a partner, kissing, and sexual intercourse. This study also found that adolescents' perceived maternal approval was greater than actual maternal approval for both genders, suggesting that adolescents see mothers as being more supportive of their sexual behaviors than they actually are (Bouris et al, 2012). Latino adolescents' perception that their mothers approved of their sexual behaviors parallels research among American Indian youth.…”
Section: Family Influencessupporting
confidence: 56%
“…Similarly, LGB youth who experienced family rejection were 3.4 times as likely to use illicit substances (Ryan et al, 2010). However, no studies used valid measures of family support or rejection within the context of the LGB experience, and further research is needed to understand this dynamic relationship (Bouris et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a way to distinguish parental attitudes about the dating realm is to assess whether they caution their children to delay dating or appear more accepting of this particular transition (Bouris et al, 2012). Parents may vary further in their imposition of dating-specific rules and restrictions .…”
Section: Parental Negativity About Dating and Intimate Partner Violencementioning
confidence: 99%